Studying, translating, and editing the greek fathers in Lorenzo’s Florence: Pico, Poliziano, and Ficino - Bastitta Harriet, Francisco (2025)
Fil: Bastitta Harriet, Francisco. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras; Argentina